SUPERVISION OF PARSTOCK STORAGE BY CHEF PASTRY AT GRAND ELITE HOTEL PEKANBARU - Winna Amelian Wernanda; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Grand Elite Hotel Pekanbaru which is located on Jl. Riau is one of the 4-star hotels that are in great demand by guests for the purpose of staying or holding event meetings. At Grand Elite Hotel Pekanbaru, there is a pastry section that provides various kinds of cakes for guest companions at breakfast and also serves as a coffee break during event meetings. This pastry section always produces cakes that are delicious and attractive in appearance to be served, this is supported by good processing and storage from the pastry staff at Grand Elite Hotel Pekanbaru. Therefore, storage must always be considered and supervised by the pastry chef so that there is no material damage that results in reduced quality of the resulting product. This study was conducted to determine the supervision of parstock storage by pastry chefs at Grand Elite Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. Data obtained from in-depth interviews with pastry chefs, executive chefs as well as direct observation and documentation. Then the data obtained were analyzed to obtain conclusions. The results of this study indicate that the pastry chef must supervise the work of other employees in storing ingredients Keywords : Hotel,Storage,Parstock,Pastry